2020
DOI: 10.3390/ijms21186561
|View full text |Cite
|
Sign up to set email alerts
|

Is There Evidence for IGF1R-Stimulating Abs in Graves’ Orbitopathy Pathogenesis?

Abstract: In this review, we summarize the evidence against direct stimulation of insulin-like growth factor 1 receptors (IGF1Rs) by autoantibodies in Graves’ orbitopathy (GO) pathogenesis. We describe a model of thyroid-stimulating hormone (TSH) receptor (TSHR)/IGF1R crosstalk and present evidence that observations indicating IGF1R’s role in GO could be explained by this mechanism. We evaluate the evidence for and against IGF1R as a direct target of stimulating IGF1R antibodies (IGF1RAbs) and conclude that GO pathogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“… 37 However, the interactions between TSHR and IGF-1R are complex, with immunoglobulins binding directly to TSHR. 9 , 38 Based on its important role in TAO, this study selected TSHR as the positive target during SELEX. Aptamer detection of TSHR expression showed that this receptor correlated positively with disease activity of disease, with results consistent with those obtained using anti-TSHR antibody, but at much lower cost.…”
Section: Discussionmentioning
confidence: 99%
“… 37 However, the interactions between TSHR and IGF-1R are complex, with immunoglobulins binding directly to TSHR. 9 , 38 Based on its important role in TAO, this study selected TSHR as the positive target during SELEX. Aptamer detection of TSHR expression showed that this receptor correlated positively with disease activity of disease, with results consistent with those obtained using anti-TSHR antibody, but at much lower cost.…”
Section: Discussionmentioning
confidence: 99%
“…A role for IGF-1R in the pathogenesis of GO has been proposed, but the presence and function of IGF-1R antibodies (IGF-1R Abs) are controversial ( 82 ). The findings of Marcus-Samuels et al.…”
Section: Autoantibodies In Go Pathogenesismentioning
confidence: 99%
“…As the study progressed, researchers found that IGF-1R can also be involved in GO pathogenesis through the IGF-1R/TSHR crosstalk pathway, where GO Igs activate crosstalk by binding to TSHR on OFs ( 46 ). Kriege et al.…”
Section: Immune Factorsmentioning
confidence: 99%
“…Thus, TSHR and IGF-1R can form physical and functional protein complexes. It has been shown that IGF-1R and TSHR can interact to increase signaling when activated by their respective ligands, and that inhibition of IGF-1R activity blocks signaling downstream of TSHR ( 46 ). IGF-1R/TSHR signaling also boosts the production of hyaluronan in GO OFs and other glycosaminoglycan components in the ECM ( 48 ) ( Figure 2 ).…”
Section: Immune Factorsmentioning
confidence: 99%